IMPROVING URBAN DEVELOPMENT METHODS FOR THE DEVELOPMENT OF AN URBAN TRANSPORT SYSTEM - Oleg NIKIFOROV (Silesian University of Technology, 2021)
The problems of modern urban planning are described and ways to solve these are discussed. Cities of the Russian Federation have low indicators of transport and planning efficiency; the general plan theory of the city does not answer many questions on the development of the urban environment. There are no requirements for the efficient use of urban areas and the formation of a city plan. An integrated approach is considered to improve the productivity of transport infrastructure to the modern level of motorization, develop measures to improve road safety, and also enable the prioritized development of environmentally friendly, economical, and high-speed types of public passenger transport. In this respect, the problems of improving the theory and practice of urban planning are highlighted in a new light. During the period of preparation of this article for publication, a new master plan for the development of the city of Omsk was approved, which included these proposals. The construction of the longest embankment in Eurasia began; a decision was made to use tunnels and stations of the unfinished metro for the development of tram routes.